Pelatihan Pembuatan Media Pembelajaran Berbasis Kecerdasan Artifisial Di Madrasah Aliyah Negeri 11 Jakarta - Agung Wijoyo; Indra Cahya Firdaus; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2024)
Training in creating learning media based on artificial intelligence (AI) at Madrasah Aliyah Negeri (MAN) 11 Jakarta aims to increase teacher competence in providing innovative and adaptive learning to technological developments. This activity involves teachers from various fields of study who are given intensive training on the use of AI-based tools, such as applications for creating interactive videos, dynamic presentation materials, and learning analysis platforms. Training methods include workshops, interactive discussions, and classroom application simulations. The results of the training show an increase in teachers' understanding of the concepts and applications of AI in learning, as well as encouraging creativity in designing media that is relevant and interesting for students. This training is expected to support the transformation of learning at MAN 11 Jakarta towards 21st century education which focuses on technological literacy and developing students' critical skills Keywords: artificial, teacher, writing, education, competence, professionalism.